Project-based action in the structure of educational-game environments - N.V. Gromyko; Y.V. Gromyko; S.P. Usoltsev (Культурно-историческая психология, 2025)
Context and relevance. The article describes an approach to creating educational-game environments aimed at developing project-based thinking. Currently, the problem of declining motivation among school students in the context of the modern education system, which is heavily focused on preparing for the Unified State Exam (USE) and Olympiads, is widely recognized. The authors emphasize the importance of rekindling interest in knowledge and fostering curiosity in the learning process. As one of the effective solutions to this problem, the use of game-based learning methods, which are increasingly being applied in educational practice, is considered. However, the authors argue that existing game formats fail to incorporate project-based activities into the gameplay, which is crucial for development of project-based thinking among high school students. The authors propose a new approach to creating an educational-game environment that not only sustains interest in learning but also promotes the development of project-based thinking. The article describes a technology for transforming a traditional board game into a project-based game, enabling students not only to acquire theoretical knowledge but also to engage in solving real scientific problems. As an example, the educational-game module "Life on the Moon" is presented, within which students develop a project for an experimental setup to sustain a colony of prokaryotes on the Moon. Unlike a full-fledged cycle of project activities—whose minimum duration is one academic year—the educational-game module is conducted in three days. The proposed module can be used either as a propaedeutic course in project activity or as an intensive course, which allows students to study several fragments of the project activity cycle—such as proposing a project idea, re-analyzing the situation, and transforming the project idea into a system of tasks—more thoroughly. The article highlights the importance of project-based activities as a leading activity for high school students and offers specific methodological recommendations for organizing game processes aimed at developing project-based thinking. The authors also draw attention to the need for changes in pedagogical professionalism in the context of increasing gamification of education.